Epidemiology and sex differences of podoconiosis in Ethiopia: A systemic review and meta-analysis - Brhane Berhe; Haftom Legese; Fitsum Mardu; Kebede Tesfay; Gebre Adhanom; Tsega Kahsay; Getachew Belay; Hadush Negash (Heliyon, 2021)
Objectives: Podoconiosis is a poorly understood neglected tropical disease which results in a high socio-economic burden. In Ethiopia, despite the high prevalence, morbidity, and socio-economic impacts, little information is available about the disease. Thus, this review aimed to assess the effect of sex differences and pooled prevalence of podoconiosis in Ethiopia. Study setting: Ethiopia is a country located in East Africa. Methods: Published literature on the prevalence of podoconiosis in Ethiopia was searched through MEDLINE/PubMed, Cochrane Library, Goggle scholar, and Global Health. Studies conducted in humans, open access, and met 50% threshold on the quality assessment checklist score adopted from Joanna Briggs Institute were eligible for inclusion. Data were extracted using first author, year of publication, participants' population, setting (urban/rural), study design, podoconiosis infection among males, the total number of males, podoconiosis infection among females, the total number of females, and context using Microsoft™ Excel. R statistical software version 3.6.1 was utilized to carry out the meta-analysis. The protocol of this review is registered in the PROSPERO international prospective register of systematic reviews and assigned a registration number of CRD 42020154697. Results: We performed heterogeneity, sensitivity, and publication bias analysis for the included articles. We identified 229 records, of which 11 studies met the inclusion criteria. The pooled prevalence of podoconiosis in Ethiopia was 6% [95% CI: 5%; 6%]. Subgroup analysis by setting indicated slightly higher prevalence in rural settings. The odds of podoconiosis infection among female is 1.15 times that of males'' The effect of sex on podoconiosis was sub-grouped by study setting and the odds of females were 1.29 times at increased risk of acquiring podoconiosis than males (p < 0.01) in rural settings. Conclusions: The prevalence of podoconiosis in Ethiopia is high. This review suggested that females are at higher risk of developing podoconiosis than males, particularly in rural communities which has health promotion and awareness implications regarding protective wear.